2020
DOI: 10.3390/diagnostics10080545
|View full text |Cite
|
Sign up to set email alerts
|

Aldosterone-Mediated Sodium Retention Is Reflected by the Serum Sodium to Urinary Sodium to (Serum Potassium)2 to Urinary Potassium (SUSPPUP) Index

Abstract: The serum sodium to urinary sodium ratio divided by the (serum potassium)2 to urinary potassium ratio (SUSPPUP formula) reflects aldosterone action. We here prospectively investigated into the usefulness of the SUSPPUP ratio as a diagnostic tool in primary hyperaldosteronism. Parallel measurements of serum and urinary sodium and potassium concentrations (given in mmol/L) in the fasting state were done in 225 patients. Of them, 69 were diagnosed with primary aldosteronism (PA), 102 with essential hypertension (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…None of the diagnosed PA patients was hypokalemic at screening. A study by Kanaan et al showed that a po-tassium concentration of 3.8 mmol/L or lower (" < 3.9 mmol/L") best-discriminated patients with PA from with EH when only this information is available [15]. In our study, 5 (45.5 %) of patients with PA had a serum-K below 3.9 mmol/L compared to 48 (26.7 %) (p = 0.179) of the non-PA subjects.…”
Section: Incidence Of Primary Aldosteronism In the Study Populationmentioning
confidence: 99%
“…None of the diagnosed PA patients was hypokalemic at screening. A study by Kanaan et al showed that a po-tassium concentration of 3.8 mmol/L or lower (" < 3.9 mmol/L") best-discriminated patients with PA from with EH when only this information is available [15]. In our study, 5 (45.5 %) of patients with PA had a serum-K below 3.9 mmol/L compared to 48 (26.7 %) (p = 0.179) of the non-PA subjects.…”
Section: Incidence Of Primary Aldosteronism In the Study Populationmentioning
confidence: 99%
“…Willenberg et al [11] and Kanaan et al [16] demonstrated increased SUSPUP and SUSPPUP ratios in patients with primary hyperaldosteronism. In such a setting, the lack of any significant differences in SUSPUP and SUSPPUP ratios (p = 0.36 and 0.35, respectively) also confirms, in our opinion, that hyperaldosteronism does not seem to play a significant role in the development of PIH.…”
Section: Discussionmentioning
confidence: 96%